Insights in the molecular mechanisms of the anti-angiogenic effect of an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase - Vincent, Loïc; Albanese, Patricia; Bompais, Heidi; Uzan, Georges; Pierre Vannier, Jean; Gabriel Steg, Philippe; Soria, Jeannette; Soria, Claudine (Thrombosis and Haemostasis, 2003)
3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) reduce the risk of coronary event by cholesterol-lowering dependent and independent mechanisms. We have already described that the inhibitory effect of cerivastatin on angiogenesis contribute to the cholesterol-independent beneficial effect and was due to the inhibition of the cell signaling cascade RhoA/FAK/Akt. In this study, new insights in the molecular mechanism of action were provided. It indicates an inhibition of exposure of alpha V beta 3 integrin on cell membrane and a modification of gene expression. The inhibition of angiogenesis could be related to 1) an increase in genes involved in the inhibition of cell proliferation (p19INK4, p21Waf/Cip1, Wnt-5a), the inhi bition of cell migration (Rho-GDI 1, α E-catenin) and 2) a downregulation of genes involved in angiogenesis (PAI-1, Vitronectin, HoxD3, Notch4) or in cell invasion (Semaphorin E). In addition, DNA repair protein genes (MLH1, XRCC1) were increased.This study may indicate new biological interest of genes involved in angiogenesis control.
Keywords: Statins; angiogenesis inhibition; RhoA; gene expression